Determinants of the incidence of non-communicable diseases and early death among lecturers at the Health Polytechnic, Ministry of Health, Jambi - Kalsum, Ummi; Gusmawati, Putri; Fitri, Adelina; Sitanggang, Hendra Dhermawan (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Non-communicable diseases (NCDs) that cause early death both in the general population and among lecturers are increasing. This study aimed to analyze factors related to NCDs, as well as early death among lecturers. Method: This study design was cross-sectional. The sample was 4 lecturers who died in the 2013-2022 period to identify causes of early death and 75 homebase lecturers for NCDs incidents at the Jambi Ministry of Health Polytechnic. Results: The number of early deaths was 4 people (1.75 person-years) and the incidence of NCDs was 17.3%. Factors associated with NCDs were workload (PR= 8.25; 95% CI= 1.96-34.61), family history (PR= 4.50; 95% CI= 1.83-11.05), stress (PR= 3.98; 95% CI=1.54-10.26) and rest patterns (PR 3.61; 95% CI 1.32-9.87). There was no relationship between diet and physical activity and the incidence of NCDs. The dominant factor was workload after controlling by family history, diet, rest patterns and stress (PR= 5.127; 95% CI=1.02-25.60). Conclusion: Lack of rest, family history, stress and workload increase the risk of NCDs and early death in lecturers. The lecturers must pay attention to their workload, implement a balanced nutritional diet, rest patterns, and stress management, especially for those with a family history of NCDs to prevent NCDs and early death.